2013
DOI: 10.5114/pm.2013.36595
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the quality of life of women before and after breast reconstruction measured with the use of EORTC QLQ-C 30 and EORTC QLQ-BR 23 scale

Abstract: StreszczenieWstęp: Około 13% Polek umiera rocznie z powodu raka piersi. Choroba ta jest pierwsza, jeśli chodzi o epidemiologię nowotworów złośliwych w Polsce wśród kobiet. Leczenie raka piersi jest coraz mniej okaleczające, ale nadal trwa długo i daje wiele objawów ubocznych. Obecnie u części kobiet, gdy nie ma przeciwwskazań, można wykonać odbudowę utraconej piersi, czyli zrekonstruować ją.Cel pracy: Badania miały na celu określenie, czy występują różnice w ocenie jakości życia u kobiet po mastektomii i rekon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The study conducted by Bąk-Sosnowska does not confirm the correlation between having a life partner with support offered by him and the fact of accepting the disease [17]. The patients with the higher education level are characterised by more optimistic evaluation of their own opportunities and more care for their health in comparison to women with lower education [18,19,31].…”
Section: Discussionmentioning
confidence: 91%
“…The study conducted by Bąk-Sosnowska does not confirm the correlation between having a life partner with support offered by him and the fact of accepting the disease [17]. The patients with the higher education level are characterised by more optimistic evaluation of their own opportunities and more care for their health in comparison to women with lower education [18,19,31].…”
Section: Discussionmentioning
confidence: 91%
“…According to many researchers, there is no relationship between the quality of life and the type of surgical treatment of breast cancer applied [28,15,29]. In their study, Miśkiewicz et al confirmed that women after mastectomy who decided against breast reconstruction had a decreased quality of life, and consequently, satisfaction with life [30].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In addition, GBC diagnoses generally elicited negative emotions among the participants in this study, which is similar to previous studies. 34,35 There were appraisals of losses of control over their own lives from their cancer diagnoses 36 and different individualized coping mechanisms that were used by women in this study.…”
Section: Liow Et Al N Discussionmentioning
confidence: 99%